Efficacy of topical anesthetics of lidocaine, benzocaine, and EMLA in reducing pain during inferior alveolar nerve block in schoolchildren: a randomized controlled trial - Mawia Karkoutly; Laila Alatassi; Lilian Azrak; Nada Bshara (BDJ Open)
Abstract Objectives This study aimed to evaluate the efficacy of 5% EMLA cream and 8% lidocaine gel in reducing pain during inferior alveolar nerve block (IANB) compared with 20% Benzocaine in children aged 6–10 years. Materials and methods This was a triple‐blinded, randomized, parallel‐group, active-controlled trial with three arms. 45 children were randomly assigned into 3 groups. Group 1: control group, 20% benzocaine gel (n = 15). Group 2: 8% lidocaine gel (n = 15). Group 3: 5% EMLA cream (n = 15). Each topical anesthetic was applied in an amount of 0.3 mL using a cotton swab for 2 min, followed by IANB administration. The following primary outcome measures were considered: pulse rate, the face, legs, activity, cry, consolability (FLACC) behavioral pain assessment scale, and the Wong-Baker FACES pain rating scale. Results The mean score of the FLACC behavioral pain assessment scale in group 2 (2.20 ± 1.86) was slightly higher, but this result was not statistically significant p = (0.806). Regarding the Wong-Baker FACES pain rating scale scores, no statistically significant difference was noted between the study groups p = (0.593). After IANB administration, the mean pulse rate was higher in group 3 (102.40 ± 14.28). However, this difference was not statistically significant p = (0.351). In addition, the mean change of the pulse rate from the baseline to this time point was not statistically significant p = (0.638), indicating a smaller physiologic response to the painful stimulus. Conclusion 8% lidocaine gel was not superior to 20% benzocaine nor 5% EMLA in reducing pain during IANB administration.